2021
DOI: 10.3390/cryptography5040037
|View full text |Cite
|
Sign up to set email alerts
|

A New Hybrid Automated Security Framework to Cloud Storage System

Abstract: The need for cloud storage grows day after day due to its reliable and scalable nature. The storage and maintenance of user data at a remote location are severe issues due to the difficulty of ensuring data privacy and confidentiality. Some security issues within current cloud systems are managed by a cloud third party (CTP), who may turn into an untrustworthy insider part. This paper presents an automated Encryption/Decryption System for Cloud Data Storage (AEDS) based on hybrid cryptography algorithms to imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…[7] CRT-RSA, HE-CRT-RSA The results obtained for encryption and decryption time of the proposed method are compared with the conventional RSA algorithm and could find that the proposed method result in good output but the level of security and authentication is not analyzed. [8] ASC, ARC, IARC The encryption and decryption time for different file sizes have been calculated comparing the results with the conventional algorithms achieving results for the proposed methodology. [9] DSA, GZIP, AES The total time saving factor is calculated for encryption and decryption before and after compression but the security levels and authentication is compromised.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[7] CRT-RSA, HE-CRT-RSA The results obtained for encryption and decryption time of the proposed method are compared with the conventional RSA algorithm and could find that the proposed method result in good output but the level of security and authentication is not analyzed. [8] ASC, ARC, IARC The encryption and decryption time for different file sizes have been calculated comparing the results with the conventional algorithms achieving results for the proposed methodology. [9] DSA, GZIP, AES The total time saving factor is calculated for encryption and decryption before and after compression but the security levels and authentication is compromised.…”
Section: Discussionmentioning
confidence: 99%
“…El-Attar et al [8] suggested the hybrid automated algorithm to maintain the confidentiality and obtain high efficiency during encryption of large files. The proposed method consists of random key generation using the RSA algorithm for generating the private keys and encrypted keys.…”
Section: Literature Surveymentioning
confidence: 99%
“…El-Attar et al [55] proposed a hybrid automated approach to preserve secrecy while achieving great efciency during the encryption of huge data. Te suggested technique comprises random key creation utilizing the RSA algorithm to generate private and encrypted keys.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Polynomial encryption technique has been the subject of several studies. In 2021, El-Attar [1] presented hybrid cryptography solutions for cloud data storage, with the purpose of enhancing data security and secrecy without depending on the CTP. ASC, ARC, and IARC are used to encrypt data chunks.…”
Section: [2] Literature Reviewmentioning
confidence: 99%